HUMANISM AS AN EXISTENTIAL AND VALUABLE IMPERATIVE IN THE CONTEXT OF INFORMATION SECURITY: SOCIAL-PHILOSOPHICAL ANALYSIS - Larissa Kh. Gazgireeva (Вестник Северо-Кавказского федерального университета, 2022)
In this article the author on the basis of a philosophical reflection considers specifics of humanism in a context of information security for overcoming the crisis of modern society spiritual life; for the first time it is given the definition to the concept «demonizing» which confirms scientific novelty of this article and a scien- tific contribution of the author to the social philosophy.